Reading Journal as a Way to Improve Students’ Reading Comprehension - Afief Fakhruddin (Universitas PGRI Semarang, 2017)
Reading journal is one way to record students’ independent learning based on text they read. This study was conducted to fnd out the students’ level of reading comprehension through some notes written in the reading journal, the extent to which the activity of writing reading journals improved students’ reading comprehension, whether the students got beneft from reading journal. There were 80 respondents coming from three different classes in Majalengka University were asked to read a text related to the subject they learned in a certain session. Then they were assigned to write a journal that records the things they had read. When this task was fnished, the lecturer ran a quiz containing related questions to check whether they really understood the content of the text. Afterwards, students were to fll in a questionnaire regarding their opinion on the impact of the reading journal toward their reading comprehension. The fndings indicate that more than half of the participants appear to understand the material well, and the task plays a certain role in improving students’ understanding in reading comprehension. The most crucial thing is that most students think they get benefit by writing the reading journal.